Knowledge management in nursing during THE SARSCoV-2 COVID-19 pandemic - Lorena Martínez-Delgado; Carlos Augusto Osorio-Marulanda; Claudia Marcela Velásquez-Jiménez; Claudia Patricia Valencia-Molina; Gladys Eugenia Canaval-Erazo; Pablo Cesar Manyoma-Velásquez; Joas Benitez-Duque (MedUNAB)
ABSTRACT Introduction. The COVID-19 pandemic posed a significant challenge for the nursing profesión and personnel involved in direct patient care, particularly in the generation and assimilation of new knowledge to provide relevant and timely care. Objective. To explore the experiences of nursing staff regarding knowledge management and its application in clinical practice for the care of patients with COVID-19. Methodology. A qualitative multiple-case study was conducted using 8 semi-structured interviews with nurses who cared for COVID-19 patients in two hospitals in Colombia. Results. The study highlights the leadership role of nurses in planning and implementing actions aimed at the creation and dissemination of knowledge. Key factors facilitating knowledge flows included the organizational structure for knowledge management, ongoing collaboration with academic institutions, and the preparedness, experience, and professional commitment of all staff members. Additionally, the ability to contextualize knowledge for the healthcare of COVID-19 patients emerged as a critical factor. This ability is particularly relevant as it represents tacit knowledge, developed collectively and interdisciplinarily through prior experiences and the essential assimilation of external information. Discussion. The findings align with other studies that emphasize the role of nursing in knowledge transfer to the entire healthcare team under adverse conditions, as well as the barriers that impede knowledge creation and access. Conclusion. The experiences of nursing staff in knowledge management underscore the profession’s leadership in educational processes, even in challenging contexts. However, the social recognition of this role remains an area that requires further strengthening. Keywords: Knowledge Management; Information Dissemination; Education, Nursing; Nursing Education Research; COVID-19.